Analysis of static equilibrium in unilateral transfemoral amputation: a case report - Silva, Vaneska de Fátima Amorim; Alves, Flávia Regina Ferreira; Martins, Cíntia Aline; Monteiro, Helen Cristina; Barbosa, Danillo; Ferreira, Monica Beatriz; Foresti, Bruno Bonfim (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: In subjects with transfemoral amputation, mechanical changes are observed due to the dependence of an artificial limb for the support of body weight associated with a loss of musculature of the lower limb, leading to compensatory movements in the hip, pelvis and trunk during gait. Objective: This study aimed to analyze two models of prosthetic feet, articulated and solid ankle cushion hell (SACH), in relation to static balance. Methodology: This is an observational and interventional case study, with a quanti-qualitative character of a transfemoral amputee. The adapted Romberg test and the evaluation with the baropometer were used. This study was approved by the research ethics committee of the South Minas Foundation’s teaching and research foundation - FEPESMIG and approved according to the number of protocol 1,826,838 and CAAE 61766416.9.0000.5111. Results: Data from the evaluation of baropodometry associated with the Romberg test for the articulated foot showed a pressure of ± 50.0%, anterior quadrant pressure of 20%, posterior quadrant pressure of ± 30.0%, a posterior quadrant distribution of ± 60.0% and an anterior quadrant distribution of ± 40.0%. On the other hand, the SACH foot data showed a pressure of 50%, anterior quadrant pressure of ± 20.0%, posterior quadrant pressure of ± 30.0%, a posterior quadrant distribution of ± 60.0%, and anterior quadrant distribution of ± 40.0%. Conclusion: The choice of foot type should take into account the individuality of the patient, as well as the application of a complete program of intervention in physiotherapy.